On the use of glyptal in palaeontology - (:unkn) unknown (The Bernard Price Institute for Palaeontological Research, 1957)
A variety of materials is normally used in different fields of technical palaeontology, such as in adhesive, reinforcement, preservative and protective capacities. This paper promotes the general use of one material, commercially known as "Glyptal" in all these fields, unless the solvent qualities of different materials are specifically needed.
Main article